2023
DOI: 10.3390/app132312780
|View full text |Cite
|
Sign up to set email alerts
|

The Mulberry Juice Fermented by Lactiplantibacillus plantarum O21: The Functional Ingredient in the Formulations of Fruity Jellies Based on Different Gelling Agents

Aleksandra Szydłowska,
Dorota Zielińska,
Barbara Sionek
et al.

Abstract: This study aimed to investigate the effects of adding probiotics, prebiotics, and different types of jelly agents on a few key quality attributes of potentially functional mulberry jellies throughout a 10-day storage period at 4 °C. Mullbery juice was separately fermented at 37 °C for 24 h using Lactiplantibacillus plantarum O21; it was a favorable matrix for the proliferation of probiotics. Lactic acid fermentation positively affected the total anthocyanin concentration of investigated products. Also, antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…They utilized this extract along with gelatin to create grape pomace jelly with a total phenolic content of 156 mgGAE/g. Szydłowska, Zielińska, Sionek, and Krajewska (2023) investigated the impact of probiotics, prebiotics, and different types of jelly agents on the quality attributes of mulberry jelly. Their findings revealed that the addition of Lactobacillus plantarum O21 and prebiotics, such as inulin and agar-agar, to the jelly formulation resulted in the proliferation of lactic acid bacteria.…”
Section: Non-starchy Jellymentioning
confidence: 99%
“…They utilized this extract along with gelatin to create grape pomace jelly with a total phenolic content of 156 mgGAE/g. Szydłowska, Zielińska, Sionek, and Krajewska (2023) investigated the impact of probiotics, prebiotics, and different types of jelly agents on the quality attributes of mulberry jelly. Their findings revealed that the addition of Lactobacillus plantarum O21 and prebiotics, such as inulin and agar-agar, to the jelly formulation resulted in the proliferation of lactic acid bacteria.…”
Section: Non-starchy Jellymentioning
confidence: 99%